Advances in Understanding Stimulus-Responsive Phase Behavior of Intrinsically Disordered Protein Polymers. Issue 23 (2nd November 2018) - Ruff, Kiersten M.; Roberts, Stefan; Chilkoti, Ashutosh; Pappu, Rohit V.
Abstract: Proteins and synthetic polymers can undergo phase transitions in response to changes to intensive solution parameters such as temperature, proton chemical potentials (pH), and hydrostatic pressure. For proteins and protein-based polymers, the information required for stimulus-responsive phase transitions is encoded in their amino acid sequence. Here, we review some of the key physical principles that govern the phase transitions of archetypal intrinsically disordered protein polymers (IDPPs). These are disordered proteins with repetitive amino acid sequences. Advances in recombinant technologies have enabled the design and synthesis of protein sequences of a variety of sequence complexities and lengths. We summarize insights that have been gleaned from the design and characterization of IDPPs that undergo thermo-responsive phase transitions and build on these insights to present a general framework for IDPPs with pH and pressure responsive phase behavior. In doing so, we connect the stimulus-responsive phase behavior of IDPPs with repetitive sequences to the coil-to-globule transitions that these sequences undergo at the single-chain level in response to changes in stimuli. The proposed framework and ongoing studies of stimulus-responsive phase behavior of designed IDPPs have direct implications in bioengineering, where designing sequences with bespoke material properties broadens the spectrum of applications, and in biology and medicine for understanding the sequence-specific driving forces for the formation of protein-based membraneless organelles as well as biological matrices that act as scaffolds for cells and mediators of cell-to-cell communication. Graphical Abstract: Highlights: Proteins can undergo phase transitions in response to changes in intensive solution parameters such as temperature, pH, and pressure. Stimulus-responsive phase transitions are derived from information encoded in amino acid sequences. Of particular interest are the stimulus-responsive phase transitions of intrinsically disordered protein polymers, which are repeats of intrinsically disordered regions. We present a conceptual framework for the phase behavior of IDPPs that connects collapse transitions of individual chains to collective phase transitions. We summarize heuristics that have emerged from recent studies regarding the sequence determinants of stimulus-responsive phase transitions for IDPPs.